GAMBARAN FUNGSI KOGNITIF PADA LANSIA PENDERITA HIPERTENSI - Pratiwi Afriani Hamid; Reni Zulfitri; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is a health problem that occurs in elderly which can cause various complications, like a cognitive function disorders. This study aims to know the description cognitive function on elderly people with hypertension in public health center area in Payung Sekaki, Pekanbaru. The design of research was desriptive with the sample of this research were 86 persons using purposive sampling technique. Mini Mental State Examination (MMSE) applied to measure cognitive which has been stated valid. The research showed that the majority of research subject 60-74 years (erderly) old were 64 respondents (74,4%), 53 respondents (61,6%) were women, 79 respondents (91,9%) were moslems, 40 respondents (46,5%) were minangness, 44 respondents (51,2%) were elementary background, 47 respondents (54,7%) were already widower, 52 respondents (60,5%) were not answer. Respondents with elderly hypertension dont be controlled impaired cognitive function were 32 respondents (59,3%), a history not routine health control impaired cognitive function were 27 respondents (60,0%), while on the time of getting hypertension that impaired cognitive function were at (≥5 years) consist of 42 respondents (89,4%). It is recommended that health workers can provide health education like the importance of contolling blood pressure, early detection of impaired cognitive function and memory exercises to improve cognitive function in elderly hypertension.Keywords:cognitive function, elderly, hypertension